Willow seedlings from photooxidized seeds accelerate cotyledon death and anticipate first leaf emergence: a histological and biochemical study following germination - Roqueiro, Gonzalo; Causin, Humberto Fabio; Ollé Resa, Carolina Patricia; Maroder, Horacio; Maldonado, Sara Beatriz (Wiley, 2019)
In willow seeds, photooxidative damage is mainly restricted to the outer cotyledonary tissues, significantly reducing normal germination. Here we analyzed the damage generated in cotyledonary tissues and investigated whether the increase in reactive oxygen species (ROS) generation in seedlings from photooxidized seeds can affect the morphogenetic capacity of the shoot apical meristem. Seeds were photooxidized under different light intensities and the evolution of the damage during seedling growth was studied by light and transmission electron microscopies. The level of lipid peroxidation and changes in antioxidant capacity were measured following the time course of superoxide dismutase, catalase, ascorbate peroxidase and guaiacol peroxidase enzyme activities, and the effect of photooxidative stress on the genesis of new leaf primordia and lateral roots was examined. Early and active endocytosis and autophagy, changes in chloroplast morphology, as well as the accumulation and diffusion of ROS all play important roles in the early cell death observed in cotyledonary tissues. Following germination, seedlings from photooxidized seeds anticipated the emergence of first leaves, which complemented the altered functionality of the damaged cotyledons.